(untitled) (Anuario Español de Derecho Internacional, 2019)
The beginning of modern history and the subsequent war in Bosnia and Herzegovina coincide with the institutional beginnings of the European Union common foreign and security policy. At that time, Europe did not have a single position, nor could it have achieved a political consensus on any issue. In addition, it lacked appropriate instruments, as well as readiness and willingness to actively engage to put an end to war in BiH. The war in BiH was stopped, however, thanks to the efforts of the United States. This was a crucial moment for Europe to modify its common foreign and security policy. The European Union has passed a thorny path of establishing common foreign and security policy. On this path, however, the EU has experienced some progress and achieved good results, although not sufficient, just as BiH has made some progress in reforms. In order for BiH to joint the family of modern democratic countries, it will need a stronger engagement of the European Union and its more decisive common foreign and security policy, because only together we can cope with global challenges. Peace and prosperity in Bosnia and Herzegovina will also help build free and stable Europe.